Examining operational challenges and external factors influenceing the Garden City Multi-Purpose Cooperative in Guiguinto, Bulacan - Pineda, Carlos Joaquin D.; Tumangan, John Neil D.A.; De Leon, Patrick C. (Pampanga University of the Philippines Diliman Extension Program in Pampanga, 2025)
This study examined operational challenges and the influence of negative externalities on plant nursery businesses within the Garden City Multi-Purpose Cooperative, Guiguinto, Bulacan. The research investigated how external factors--traffic congestion, flooding and infrastructure limitations-- and internal aspects like marketing and financial literacy impact these businesses. Economic concepts of opportunity cost, externalities, market failure, and organizational persistence framed the study. Data were collected through surveys and interviews with ten plant nursery owners-- five cooperative, five non-members--via purposive sampling. Specifically, it aimed to (1) measure revenue losses or opportunity costs due to traffic, (2) describe how plant nursery businesses cope with traffic congestion, and (3) identify additional operational challenges.

Findings revealed that (1) estimated aggregate revenue losses from traffic congestion for January-December 2024, excluding the one (1) outlier plant owner, amounted to Php2,377,366.67; (2) businesses coped by reducing expenses, limiting inventory, leveraging personal resources, and exploring alternative marketing; and (3) key challenges included low visibility, declining customer visits, rising operational costs, flooding, limited digital marketing knowledge, and lack of financial literacy. Cooperative nurseries, less visible and susceptible to flooding, faced greater financial difficulties. Highway nurseries remained profitable despite higher traffic losses, due to greater reach and sales volume (costs and returns analysis). Persistence, especially in the cooperative, linked to sunk costs and community ties, influenced owners to continue despite strain.

Recommendations include policymakers addressing multifaceted challenges via improved infrastructure (traffic management, flood solutions). Nursery owners, particularly cooperative members, should prioritize adaptation (e-commerce, digital marketing, financial literacy assistance) to mitigate constraints. Future research should examine the "plantitos/plantitas" trend for industry revitalization and address study limitations by expanding the sample and refining analyses.
Thesis (Business Economics) UPDEPP, 2025
Keywords: Botanical gardens -- Economic aspects -- Philippines